Análisis comparativo entre las tecnologías Tesseract OCR y Abbyy FineReader, para determinar cuál ofrece la mejor eficiencia y velocidad en la digitalización masiva de documentos variados. - Ronquillo Duche, Gerson Daniel (2024)
This study presents a comparative analysis between two prominent optical character recognition (OCR) technologies, Tesseract OCR and Abbyy FineReader, with the objective of determining which offers the best efficiency and speed in mass digitization of various documents. A comprehensive evaluation of both technologies was conducted using a representative sample of documents including contracts, reports, forms, and other formats common in business and government environments. The main variables measured were text recognition accuracy, processing speed, and adaptability to different document formats. Standard OCR metrics were applied, such as character and word error rate, as well as the time required to digitize batches of documents. Additionally, detailed surveys and comparative analyzes were conducted to evaluate the adaptability of each technology. The results show that Abbyy FineReader significantly outperforms Tesseract OCR in terms of accuracy, processing speed, and adaptability to different document formats, making it the preferred choice for mass scanning in business and government environments.